1993
DOI: 10.1037/0033-2909.113.2.362
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of severe burn injuries.

Abstract: Severe burn injuries provide researchers with an opportunity to study the effects of painful but usually transient trauma on psychological functioning. To that end, this article presents a review of the 3 main areas of this body of literature: (a) premorbid characteristics of people who sustain severe burn injuries, (b) psychological reactions during hospitalization, and (c) long-term adjustment. The general implications of these studies are discussed and then used to illuminate the circumstances under which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
168
0
10

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(183 citation statements)
references
References 114 publications
4
168
0
10
Order By: Relevance
“…This rapid response is brought about by sudden increases in sympathetic nervous system activity and endogenous stress hormone levels [14,50]. It has been reported that the secretions of plasma cortisol, adrenocorticotropic hormone, and aldosterone are significantly increased immediately after severe burns, and the extent of this is associated with intensity of stress [14,40]. Furthermore, the levels of blood glucose, insulin, and cortisol in burn patients are enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This rapid response is brought about by sudden increases in sympathetic nervous system activity and endogenous stress hormone levels [14,50]. It has been reported that the secretions of plasma cortisol, adrenocorticotropic hormone, and aldosterone are significantly increased immediately after severe burns, and the extent of this is associated with intensity of stress [14,40]. Furthermore, the levels of blood glucose, insulin, and cortisol in burn patients are enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the levels of blood glucose, insulin, and cortisol in burn patients are enhanced. In patients with large areas of burn, particularly thirddegree burns, lasting hyperglycemia and hypermetabolism promote secretion from Islets of Langerhans to accelerate glycogenolysis, which elevate blood glucose [14,25,40,51]. Increased levels of cortisols are further associated with enhanced hepatic gluconeogenesis and a reduced insulinmediated glucose uptake into skeletal muscle and adipose tissue [20,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to mental images, all patients who responded described 'negative scarring-related images.' This may reflect patients' awareness of the perceived importance of the face in social interactions and other people's feeling and stigma when confronted with visible difference [7,[11][12]. Finally, 81% of patients described 'negative emotions' (anxiety, shock, sadness), 31% detailed 'positive emotions' (relief, feeling grateful) and 15% described 'feeling neutral' when they looked at themselves for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma associated with changes to appearance may be one of the most difficult challenges in adjusting to burn injuries [7]. Within the wider disfigurement literature, it has been concluded that premorbid and continuing psychological and social factors are better predictors of post-burn coping and adjustment rather than the objective characteristics of the burn injury itself.…”
Section: Introductionmentioning
confidence: 99%